Tau tubulin kinase 1 and 2 regulate ciliogenesis and human pluripotent stem cells-derived neural rosettes - Binó, Lucia; Čajánek, Lukáš (Scientific reports, 2023)
Primary cilia are key regulators of embryo development and tissue homeostasis. However, their mechanisms and functions, particularly in the context of human cells, are still unclear. Here, we analyzed the consequences of primary cilia modulation for human pluripotent stem cells (hPSCs) proliferation and differentiation. We report that neither activation of the cilia-associated Hedgehog signaling pathway nor ablation of primary cilia by CRISPR gene editing to knockout Tau Tubulin Kinase 2 (TTBK2), a crucial ciliogenesis regulator, affects the self-renewal of hPSCs. Further, we show that TTBK1, a related kinase without previous links to ciliogenesis, is upregulated during hPSCs-derived neural rosette differentiation. Importantly, we demonstrate that while TTBK1 fails to localize to the mother centriole, it regulates primary cilia formation in the differentiated, but not the undifferentiated hPSCs. Finally, we show that TTBK1/2 and primary cilia are implicated in the regulation of the size of hPSCs-derived neural rosettes.
Keywords: cilie; proteiny hedgehog; protein-serin-threoninkinasy; Hedgehog Proteins; Protein Serine-Threonine Kinases; Humans; Pluripotent Stem Cells; lidé; centrioly; Centrioles; pluripotentní kmenové buňky; Cilia